Prepregs, laminates and moulded articles

The prepreg and laminate configuration with reinforcing fibers, epoxy resin, and thermoplastic resin addresses the challenges of joining complex shapes by enhancing bonding strengths, enabling efficient and cost-effective manufacturing of structural materials.

JP7615683B2Active Publication Date: 2025-01-17TORAY INDUSTRIES INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020542924
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-23
Filing Date
2020-05-15
Publication Date
2025-01-17
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

Fiber-reinforced composite materials face challenges in joining complex shapes in a single molding process due to mechanical and adhesive methods that prolong manufacturing time and reduce material strength, while thermoplastic resin welding lacks reliability in bonding strengths, especially under impact and out-of-plane tensile modes.

Method used

A prepreg and laminate configuration using reinforcing fibers, epoxy resin, and thermoplastic resin, with specific epoxy values and fiber placement across resin interfaces, enabling efficient welding and enhanced bonding strengths, including tensile shear, out-of-plane tensile, and impact joint strengths.

Benefits of technology

The solution allows for rapid joining of composite materials with improved bonding strengths, reducing manufacturing time and costs, and producing laminates suitable for structural applications with enhanced mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615683000005
    Figure 0007615683000005
  • Figure 0007615683000006
    Figure 0007615683000006
  • Figure 0007615683000001
    Figure 0007615683000001
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a prepreg which has excellent binding strength and an excellent interlayer fracture toughness value, which can be firmly integrated with other structural members when being melted and adhered thereto, and which is for manufacturing a laminate that is suitable as a structural material; and said laminate. This prepreg contains [A] reinforced fibers, [B] epoxy resins, and [C] a thermoplastic resin as components, wherein the average epoxy value of all the epoxy resins contained in [B] is 2.0-5.0 meq. / g, [C] is present in the surface of the prepreg, and [A] the reinforced fibers included in both a resin region containing [B] and a resin region containing [C] are present across the boundary surface between the two resin regions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a prepreg containing reinforcing fibers, an epoxy resin, and a thermoplastic resin, and a laminate and a molded article containing reinforcing fibers, a thermoplastic resin, and a cured epoxy resin. [Background technology]

[0002] Fiber-reinforced composite materials, which are made by combining a thermosetting resin or a thermoplastic resin as a matrix with reinforcing fibers such as carbon fiber or glass fiber, have excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance while being lightweight, and have been applied to many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods. However, these fiber-reinforced composite materials are not suitable for manufacturing parts or structures with complex shapes in a single molding process, and in the above applications, it is necessary to prepare a member made of the fiber-reinforced composite material and then integrate it with the same or different members. Mechanical joining methods such as bolts, rivets, and screws, and joining methods using adhesives are used as methods for integrating the same or different members with fiber-reinforced composite materials made of reinforcing fibers and thermosetting resins. Mechanical joining methods require a process of pre-processing the joint parts, such as drilling holes, which leads to a long manufacturing process and increased manufacturing costs, and there is also the problem that the material strength is reduced due to the drilling of holes. Bonding methods that use adhesives require a bonding process that includes preparing the adhesive and applying the adhesive, as well as a curing process, which lengthens the manufacturing process time. This has led to problems with the adhesive strength and reliability not being fully satisfactory.

[0003] Fiber-reinforced composite materials that use a thermoplastic resin as a matrix can be used to join components by welding in addition to the mechanical joining methods and joining methods using adhesives mentioned above, which may reduce the time required to join components. However, the joining strength required for structural materials includes joining strength in tensile shear (in-plane shear) or out-of-plane tensile modes, and joining strength against impact, but there has been an issue in which sufficient reliability cannot be obtained for all of these joining strengths.

[0004] Here, Patent Document 1 discloses a method for bonding a fiber-reinforced composite material made of a thermosetting resin and reinforcing fibers via an adhesive.

[0005] Patent Document 2 shows a method for integrating a member made of a thermoplastic resin with a member made of a fiber-reinforced composite material made of a thermosetting resin. That is, a thermoplastic resin film is laminated on the surface of a prepreg sheet made of reinforcing fibers and a thermosetting resin, and a fiber-reinforced composite material is obtained by heating and pressing. The obtained fiber-reinforced composite material is then placed in a mold, and the thermoplastic resin is injection-molded to bond the thermoplastic resin member formed by injection molding to the fiber-reinforced composite material.

[0006] Furthermore, Patent Document 3 discloses a method for producing a laminate in which a thermoplastic resin adhesive layer is formed on the surface of a composite material made of a thermosetting resin and reinforcing fibers, and describes that the laminate exhibits an adhesive effect with other components via the thermoplastic resin.

[0007] Patent Document 4 discloses a prepreg in which particles, fibers, or a film made of a thermoplastic resin are disposed on the surface layer of a prepreg made of reinforcing fibers and a thermosetting resin, and also discloses a fiber-reinforced composite material thereof. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-161801 A [Patent Document 2] Japanese Patent Application Publication No. 10-138354 [Patent Document 3] Patent No. 3906319 [Patent Document 4] Japanese Patent Application Publication No. 8-259713 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the technique disclosed in Patent Document 1 is a method of bonding fiber-reinforced composite materials made of reinforcing fibers and thermosetting resins with an adhesive, and since the thermosetting resin is a matrix resin, welding cannot be applied as a method of bonding between fiber-reinforced composite materials as it is. Since it takes time for the adhesive to harden, there is a problem that the bonding process takes time, and furthermore, the bond strength achieved is insufficient.

[0010] In the method described in Patent Document 2, the bonding strength at the bonded portion between the thermosetting resin and the thermoplastic resin film in the fiber reinforced composite material was insufficient.

[0011] The fiber-reinforced composite material according to Patent Document 3 can be integrated by welding via a thermoplastic resin and exhibits excellent static bonding strength, but the bonding strength against impact is insufficient.

[0012] Patent Document 4 shows that the interlaminar fracture toughness value can be improved by using particles, fibers, or films made of a thermoplastic resin, but this method does not provide sufficient bonding strength at the boundary between the thermosetting resin and the thermoplastic resin in the fiber-reinforced composite material.

[0013] Therefore, an object of the present invention is to provide a prepreg, a laminate, and an integrally molded product which can be joined by welding to the same or different members, exhibits excellent tensile shear bonding strength, out-of-plane tensile bonding strength, and impact bonding strength, and provides a laminate suitable as a structural material. [Means for solving the problem]

[0014] In order to solve such problems, the prepreg of the present invention has the following configuration: A prepreg containing the following components [A], [B], and [C], in which the average epoxy value of all epoxy resins contained in [B] is 2.0 meq. / g or more and 5.0 meq. / g or less, [C] is present on the surface of the prepreg, and reinforcing fibers of [A] contained in both resin regions are present across the boundary between a resin region containing [B] and a resin region containing [C]. [A] Reinforced fiber [B] Epoxy resin [C]Thermoplastic resin Furthermore, the laminate of the present invention has the following configuration: That is, a laminate including layers containing the following components [A], [C], and [D], in which the average epoxy value of all epoxy resins contained in [D] is 2.0 meq. / g or more and 5.0 meq. / g or less, and reinforcing fibers of [A] contained in both resin regions are present across the boundary between a resin region containing [C] and a resin region containing [D]. [A] Reinforced fiber [C]Thermoplastic resin [D] Epoxy resin cured material Effect of the Invention

[0015] The prepreg of the present invention uses an epoxy resin and a thermoplastic resin, and the two are firmly bonded together. In addition, good welding with the same or different members is possible. Therefore, compared to conventional fiber-reinforced composite materials consisting of thermosetting resins and reinforcing fibers, the time required for the bonding process can be shortened, and the molding of structural members can be accelerated. Furthermore, the laminate exhibits excellent tensile shear bonding strength, out-of-plane tensile bonding strength, and impact bonding strength, and is excellent as a structural material. The laminate of the present invention shows excellent performance as a structure by being applied to aircraft structural members, windmill blades, automobile structural members, and computer applications such as IC trays and notebook computer housings, and the like. In addition, by using the prepreg of the present invention, it is possible to greatly reduce the molding time and molding cost of products related to the above applications. [Brief description of the drawings]

[0016] [Figure 1] 3 is a schematic diagram of a prepreg or laminate according to the present invention, showing a cross section perpendicular to the plane of the prepreg or laminate according to FIG. 2. [Diagram 2] FIG. 1 is a schematic diagram of a cross section perpendicular to a prepreg plane or a laminate plane in the present invention, which helps to explain the method of measuring the roughness average length RSm and the roughness average height Rc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The reinforcing fibers of the component [A] used in the present invention include glass fibers, carbon fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and basalt fibers. These may be used alone or in combination of two or more types. These reinforcing fibers may be surface-treated. Examples of surface treatments include metal deposition treatment, treatment with a coupling agent, treatment with a sizing agent, and additive attachment treatment. These reinforcing fibers also include conductive reinforcing fibers. As the reinforcing fibers, carbon fibers, which have a low specific gravity, high strength, and high elastic modulus, are preferably used.

[0018] Commercially available carbon fibers include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T700S-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T1100G-24K (all manufactured by Toray Industries, Inc.).

[0019] The form and arrangement of the reinforcing fibers can be appropriately selected from those in which the reinforcing fibers are arranged in one direction, a laminate of reinforcing fibers arranged in one direction, or a woven fabric, etc., but in order to obtain a laminate that is lightweight and has a higher level of durability, it is preferable that the reinforcing fibers in each prepreg be in the form of continuous fibers such as long fibers (fiber bundles) arranged in one direction or a woven fabric.

[0020] The reinforcing fiber bundle may be composed of a plurality of fibers of the same form, or may be composed of a plurality of fibers of different forms. The number of reinforcing fibers constituting one reinforcing fiber bundle is usually 300 to 60,000, but considering the production of the base material, it is preferably 300 to 48,000, more preferably 1,000 to 24,000. It may be within a range that is a combination of any of the above upper limits and any of the above lower limits.

[0021] For the reinforcing fiber of the component [A], it is preferable that the strand tensile strength measured according to the resin-impregnated strand test method of JIS R7608 (2007) is 5.5 GPa or more, since a laminate having excellent bonding strength in addition to tensile strength can be obtained. It is even more preferable that the strand tensile strength is 5.8 GPa. The bonding strength referred to here refers to the tensile shear bonding strength measured according to ISO4587:1995 (JIS K6850 (1994)) and the out-of-plane tensile bonding strength measured according to ASTM D7291-07.

[0022] The component [B] used in the present invention is an epoxy resin, and the average epoxy value of all the epoxy resins contained therein is 2.0 meq. / g or more and 5.0 meq. / g or less. Here, the average epoxy value of all the epoxy resins contained therein is calculated as follows, for example, when two components, epoxy resin 1 and epoxy resin 2, are contained. Average epoxy value (meq. / g) = (parts by mass of epoxy resin 1 / epoxy equivalent of epoxy resin 1 + parts by mass of epoxy resin 2 / epoxy equivalent of epoxy resin 2) / (parts by mass of epoxy resin 1 + parts by mass of epoxy resin 2) x 1000 Here, the epoxy equivalent refers to a value determined by the method described in JIS K7236 (2009). When the average epoxy value of all the epoxy resins contained is 2.0 meq. / g or more and 5.0 meq. / g or less, the laminate or molded product exhibits excellent tensile shear bond strength, out-of-plane tensile bond strength, and impact bond strength. Furthermore, in a more preferred embodiment, the average epoxy value of all the epoxy resins contained is 2.5 meq. / g or more and 4.0 meq. / g or less. The range may be a combination of any of the upper and lower limits above.

[0023] The composition containing the component [B] in the prepreg of the present invention preferably has a bending break strain of 8% or more when the degree of cure is 90% or more, and when such a cured product is contained in the laminate of the present invention, the impact joint strength when the laminate is joined to a member is excellent, which is preferable. That is, in the laminate of the present invention, the bending break strain of the cured epoxy resin of the component [D] is preferably 8% or more.

[0024] The bending strain at break can be determined by a three-point bending test based on JIS K7171 (1994). When determining the bending strain at break when the degree of cure of the component [B] contained in the prepreg is 90% or more, or the bending strain at break of the component [D] contained in the laminate, the type of epoxy resin is specified, and the same type of uncured resin is made into a composition in the same manner as in the measurement of the degree of cure described below, cured, and subjected to the measurement of the bending strain at break. In addition, the upper limit of the bending strain at break is not particularly limited, but the upper limit of the bending strain at break for ordinary epoxy resin cured products is 100%.

[0025] In order to bring the component [B] to a state of 90% or more cure, the epoxy resin of the component [B] and the epoxy resin composition specified as the curing agent before curing can be heated and cured under specified conditions. Heat curing under specified conditions refers to first heating at 135°C for 2 hours or 180°C for 2 hours, and then further heating as necessary until the degree of cure reaches 90% or more. The degree of cure of the epoxy resin cured product obtained by heating at 135°C for 2 hours or 180°C for 2 hours is measured, and if the degree of cure is 90% or more, the epoxy resin cured product can be used for characteristic evaluation. If the degree of cure is less than 90% at the heating temperature and time of 135°C for 2 hours or 180°C for 2 hours, post-heating at 180°C for 2 hours is added to check the degree of cure. If the degree of cure is less than 90% after post-heating, heating is added in the order of 200°C for 1 hour, 220°C for 1 hour, and 240°C for 1 hour until the degree of cure reaches 90% or more. If the degree of cure does not reach 90% even after heating at 240°C for 1 hour, heating can be continued at a temperature of 300°C or less until the degree of cure reaches 90% or more, thereby obtaining the desired cured epoxy resin product, which can then be used for characteristic evaluation.

[0026] Here, the degree of cure is a value calculated by calculating the heat generation amount of each of the epoxy resin of the component [B], the epoxy resin composition before curing specified as the curing agent, and the cured product of the epoxy resin as the area of ​​each peak that appears as an exothermic reaction when performing differential scanning calorimetry at a heating rate of 10 ° C / min in an inert gas atmosphere, and then calculating it by the following formula. In addition to the component [B] contained in the prepreg, a resin having the same structure as the epoxy resin and the curing agent specified as the curing agent can also be prepared and used for measurement. Here, if the curing agent cannot be specified, 4,4'-diaminodiphenyl sulfone may be used as the curing agent in the above composition. In addition, compounds such as a curing catalyst and a viscosity modifier, which will be described later in the examples, can be preferably used as elements that can constitute the above composition, but these are not particularly limited as long as they do not affect the measurement results. Degree of cure (%)=((amount of heat generated before cure of composition containing epoxy resin)−(amount of heat generated of cured product of epoxy resin)) / (amount of heat generated before cure of composition containing epoxy resin)×100 The epoxy resin cured product of the component [D] in the present invention can be obtained by heating and curing the epoxy resin of the component [B]. Regarding the judgment of the curing of the component [D] contained in the laminate, when the laminate is subjected to differential scanning calorimetry under an inert gas atmosphere at a heating rate of 10°C / min, if the area of ​​the peak (residual heat) appearing as an exothermic reaction is 50 J / g or less, it can be judged to be a substantially cured product. Alternatively, when the epoxy resin composition before curing can be specified, the degree of curing may be calculated by the above formula, and if it is 90% or more, it may be considered to be a cured product. When the prepreg of the present invention is used, the epoxy resin corresponds to the component [B]. The laminate of the present invention does not necessarily have to be produced via a prepreg, but may be produced by a resin transfer molding method described later.

[0027] Examples of the epoxy resin used in the component [B] include bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AD ​​type epoxy resins, and bisphenol S type epoxy resins; brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether; epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins; glycidyl amine type epoxy resins such as N,N,O-aminophenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine; resorcinol diglycidyl ether; and triglycidyl isocyanurate.

[0028] The component [B] of the present invention contains 20 to 50 parts by mass of a bisphenol-type epoxy resin having an epoxy equivalent of 400 to 3000 relative to 100 parts by mass of all the epoxy resins contained, which is a preferred embodiment since it provides a laminate and a molded product with excellent impact bonding strength. A more preferred embodiment contains 20 to 50 parts by mass of a bisphenol-type epoxy resin having an epoxy equivalent of 1000 to 3000 relative to 100 parts by mass of all the epoxy resins contained.

[0029] Examples of the curing agent for the epoxy resin include dicyandiamide, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, polymercaptans, etc. Among these, the use of dicyandiamide or aromatic amine compounds is preferred because good reactivity and excellent mechanical properties and heat resistance of the cured product can be obtained. Examples of the aromatic amine compound include 3,3'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-4,4'-diaminodiphenyl sulfone, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di Examples of the alkylaminodiphenyl sulfone include isopropyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-t-butyl-5,5'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetra-t-butyl-4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, and 3,3'-diaminodiphenyl sulfone.

[0030] Furthermore, the epoxy resin of the component [B] preferably contains a thermoplastic resin component soluble in the epoxy resin in a dissolved state as a viscosity modifier. Such a thermoplastic resin component is a different thermoplastic resin component from the component [C]. Here, "soluble in the epoxy resin" refers to the presence of a temperature range in which a homogeneous phase is formed by heating or heating and stirring a mixture of the thermoplastic resin component and the epoxy resin. Here, "forming a homogeneous phase" refers to a state in which no separation is visible to the naked eye. Here, "dissolved state" refers to a state in which an epoxy resin containing a thermoplastic resin component is in a certain temperature range and forms a homogeneous phase. Once a homogeneous phase is formed in a certain temperature range, separation may occur outside that temperature range, for example at room temperature.

[0031] The thermoplastic resin component soluble in the epoxy resin of the component [B] is preferably a thermoplastic resin having a bond selected from the group consisting of carbon-carbon bond, amide bond, imide bond, ester bond, ether bond, carbonate bond, urethane bond, thioether bond, sulfone bond and carbonyl bond in the main chain. This thermoplastic resin component may have a partially crosslinked structure and may be crystalline or amorphous. In particular, at least one resin selected from the group consisting of polyamide, polycarbonate, polyacetal, polyphenylene oxide, polyphenylene sulfide, polyarylate, polyester, polyamideimide, polyimide, polyetherimide, polyimide having a phenyltrimethylindane structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyaramid, polyvinyl formal, polyvinyl butyral, phenoxy resin, polyethernitrile and polybenzimidazole is preferable.

[0032] The thermoplastic resin constituting the component [C] is not particularly limited, and examples thereof include polyester-based resins (polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, liquid crystal polyester, etc.), polyolefin-based resins (polyethylene, polypropylene, polybutylene, etc.), styrene-based resins, urethane resins, polyoxymethylene, polyamide-based resins (aliphatic polyamides such as polyamide 6 and polyamide 66, semi-aromatic polyamides, alicyclic polyamides, etc.), polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyketone, polyarylene ether ketone (polyether ketone, polyether ether ketone, polyether ketone ketone, etc.), polyarylate, polyether nitrile, phenol-based resins, and phenoxy resins. Furthermore, these thermoplastic resins may be copolymers or modified products of the above-mentioned resins, and / or resins in which two or more kinds are blended.

[0033] In order to improve impact resistance, an elastomer or rubber component may be added to the epoxy resin or thermoplastic resin. Furthermore, depending on the application, etc., the epoxy resin or thermoplastic resin may contain other fillers or additives as appropriate within the scope of the present invention. For example, inorganic fillers, flame retardants, conductive agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, coupling agents, etc. may be mentioned.

[0034] In the prepreg of the present invention, the reinforcing fibers [A] contained in both resin regions are present across the boundary surface between the resin region containing [B] and the resin region containing [C].

[0035] The presence of [A] included in both resin regions across the boundary surface of both resin regions can be confirmed by observing a cross section obtained by cutting perpendicularly to the plane direction. An example is shown in FIG. 2. In the observation image 9 in FIG. 2, in the case of a prepreg, the resin region 7 including the component [C] is in close contact with the resin region 8 including the component [B], and the surface where the resin region 7 including the component [C] and the resin region 8 including the component [B] are in close contact is illustrated as the boundary surface 10. In addition, multiple components [A] 6 exist on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 including the component [C] and the resin region 8 including the component [B]. In this way, the state in which the components [C] and [B] are in contact with the periphery of the reinforcing fiber can be said to be a state in which the reinforcing fiber is "included in both resin regions across the boundary surface."

[0036] Furthermore, when the prepreg of the present invention is viewed in plan, in a cross section perpendicular to the prepreg plane containing the fibers of [A] present across both resin regions, that is, in a cross section obtained by cutting perpendicularly to the prepreg plane direction, from a direction at an angle of 45 degrees different, regardless of whether it is clockwise or counterclockwise, with respect to the fiber direction of any [A] contained in both resin regions, it is preferable that the roughness average length RSm defined in JIS B0601 (2001) of the cross-sectional curve formed by the boundary surface between both resins is 100 μm or less and the roughness average height Rc is 3.5 μm or more.

[0037] It is also preferable that the resin region containing [B] and the resin region containing [C] are adjacent to each other in a layered state to form the boundary surface. Adjacent to each other in a layered state means that both continuous resin regions are adjacent to each other, as shown in Fig. 2, for example, and this can be confirmed by observing a cross section obtained by cutting the prepreg perpendicular to the planar direction.

[0038] The presence of the reinforcing fibers [A] contained in both resin regions across the boundary between the resin region containing the component [B] and the resin region containing the component [C] improves the strength of the resin region containing the component [C] and improves the bonding strength. The component [A] present on the boundary surface is chemically or / and physically bonded to the components [B] and [C], thereby improving the adhesion between the resin region containing the component [B] and the resin region containing the component [C]. The number of components [A] present on the boundary surface may be one or more, and the upper limit number is not particularly limited, but is 200 in the observation range described below.

[0039] The boundary surface between the resin region containing component [B] and the resin region containing component [C] is observed in a cross section perpendicular to the prepreg plane containing the fibers of [A] that exist across both resin regions, from a direction that differs by 45 degrees, regardless of whether it is clockwise or counterclockwise, with respect to any fiber direction of [A] contained in both resin regions, in a plan view of the prepreg, i.e., from a viewpoint perpendicular to the prepreg plane direction. By observing the state of the resin region at the boundary surface in such a cross section, the adhesion strength in the fiber direction and in the direction perpendicular to the fiber direction can be evaluated simultaneously.

[0040] In such cross-sectional observation, when the roughness average length RSm of the cross-sectional curve formed by the boundary surface, as defined by JIS B0601 (2001), is 100 μm or less, not only the chemical or / and physical bonding force but also the mechanical bonding force of entanglement is added, and the resin region containing the component [B] and the resin region containing the component [C] are less likely to peel off, which is preferable. The lower limit is not particularly limited, but is preferably 15 μm or more from the viewpoint of avoiding a decrease in the mechanical bonding force due to stress concentration. In addition, when the roughness average height Rc of the cross-sectional curve is 3.5 μm or more, not only the mechanical bonding force due to entanglement is expressed, but also the component [A] present on the boundary surface is chemically or / and physically bonded to the component [B] and the component [C], and the adhesive force between the resin region containing the component [B] and the resin region containing the component [C] is improved, which is preferable. A more preferred range of the average roughness height Rc of the cross-sectional curve is 10 μm or more, at which the component [A] is more likely to be included in both resin regions and the adhesive strength is further improved, and particularly preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 100 μm or less from the viewpoint of avoiding a decrease in mechanical bonding strength due to stress concentration.

[0041] Here, the method for measuring the roughness average height Rc and the roughness average length RSm of the cross-sectional curve can be a known method. For example, after curing the component [B], the method for measuring from a cross-sectional image acquired using X-ray CT, the method for measuring from an elemental analysis mapping image by an energy dispersive X-ray spectrometer (EDS), or the method for measuring from a cross-sectional observation image by an optical microscope, a scanning electron microscope (SEM), or a transmission electron microscope (TEM) can be mentioned. In the observation, the component [B] and / or the component [C] may be dyed to adjust the contrast. In the image obtained by any of the above methods, the roughness average height Rc and the roughness average length RSm of the cross-sectional curve are measured in a range of 500 μm square.

[0042] An example of a method for measuring the roughness average height Rc and roughness average length RSm of a cross-sectional curve (cross-sectional curve element measuring method 1) is shown in FIG. 2. Using an end 11 on the resin region side including the component [B] of a rectangular observation image 9 as a reference line, vertical base lines 12 are drawn at 5 μm intervals from the resin region 8 including the component [B] toward the resin region 7 including the component [C]. The point where the vertical base line drawn from the reference line first intersects with the component [C] is plotted, and the line connecting the plotted points is defined as a cross-sectional curve 13. A filtering process based on JIS B0601 (2001) is performed on the obtained cross-sectional curve 13, and the roughness average height Rc and roughness average length RSm of the cross-sectional curve 13 are calculated.

[0043] From the viewpoint of realizing excellent mechanical properties, it is preferable that the resin region containing [B] and the resin region containing [C] are adjacent to each other in a layered structure to form the boundary surface.

[0044] In the prepreg of the present invention, the weight per unit area of ​​the thermoplastic resin of the component [C] is 10 g / m 2 It is preferable that the thickness is 10 g / m or more. 2 If the thickness is more than this, a sufficient thickness for achieving excellent bonding strength can be obtained, and more preferably, 20 g / m 2 The upper limit is not particularly limited, but is preferably 500 g / m because the amount of thermoplastic resin is not too large compared to the reinforcing fibers and a laminate excellent in specific strength and specific elastic modulus can be obtained. 2 Here, the basis weight is the weight per 1 m of prepreg. 2 This refers to the mass (g) of the component [C] contained per unit.

[0045] The prepreg of the present invention has a reinforcing fiber amount per unit area of ​​30 to 2,000 g / m 2 It is preferable that the amount of reinforcing fibers is 30 g / m 2 When the amount of reinforcing fibers is 2,000 g / m or more, the number of layers required to obtain a predetermined thickness during laminate molding can be reduced, and the work can be simplified. 2 When it is equal to or less than this, the drape property of the prepreg is likely to be improved.

[0046] The reinforcing fiber mass content of the prepreg of the present invention is preferably 30 to 90 mass%, more preferably 35 to 85 mass%, and even more preferably 40 to 80 mass%. It may be a range that is a combination of any of the above upper limits and any of the above lower limits. When the reinforcing fiber mass content is 30 mass% or more, the amount of resin is not too large compared to the fibers, and the advantages of a laminate having excellent specific strength and specific elastic modulus are easily obtained, and when molding the laminate, the amount of heat generated during curing is unlikely to be excessively high. In addition, when the reinforcing fiber mass content is 90 mass% or less, impregnation failure of the resin is unlikely to occur, and the voids in the obtained laminate are likely to be reduced.

[0047] The laminate of the present invention satisfies the following requirements: It includes layers containing components [A], [C], and [D], [D] is a cured product of an epoxy resin in which the average epoxy value of all epoxy resins is 2.0 meq. / g or more and 5.0 meq. / g or less, and the reinforcing fibers of [A] contained in both resin regions are present across the boundary between a resin region containing [C] and a resin region containing [D].

[0048] The component [D] used in the present invention is a cured epoxy resin, and is a cured epoxy resin having an average epoxy value of all the epoxy resins of 2.0 meq. / g or more and 5.0 meq. / g or less, where the epoxy value is calculated as described above.

[0049] The presence of [A] across the boundary between both resin regions can be confirmed by observing a cross section obtained by cutting the laminate perpendicularly to the planar direction, similar to the confirmation method for the prepreg described above. An example is shown in FIG. 2. In the observation image 9 in FIG. 2, in the case of the laminate, the resin region 7 including the component [C] is in close contact with the resin region 8 including the component [D], and the surface where the resin region 7 including the component [C] and the resin region 8 including the component [D] are in close contact is illustrated as the boundary 10. In addition, multiple components [A] 6 exist on the boundary 10. The component [A] 6 on the boundary 10 is in contact with both the resin region 7 including the component [C] and the resin region 8 including the component [D]. In this way, the state in which the components [C] and [D] are in contact with the periphery of the reinforcing fiber can be said to be a state in which the reinforcing fiber is "included in both resin regions across the boundary."

[0050] Furthermore, when the laminate of the present invention is viewed in plan, the cross section perpendicular to the plane of the laminate containing [A] existing across both resin regions, i.e., the observed cross section obtained by cutting perpendicularly to the plane direction of the laminate, regardless of whether the fiber direction of any [A] contained in both resin regions is clockwise or counterclockwise, is preferably 100 μm or less and 3.5 μm or more in the roughness average length RSm defined by JIS B0601 (2001) of the cross section curve formed by the boundary surface where both resin regions are in close contact, and 3.5 μm or more in the roughness average height Rc. It is more preferable that the roughness average height Rc is 10 μm or more. The lower limit value of RSm and the upper limit value of Rc are not particularly limited, but from the viewpoint of the concern of a decrease in mechanical bonding force due to stress concentration, RSm is preferably 15 μm or more and Rc is preferably 100 μm or less. The roughness average height Rc and the roughness average length RSm of the cross section curve can be measured by the above-mentioned method, similar to the measurement method of the prepreg of the present invention.

[0051] From the viewpoint of realizing excellent mechanical properties, it is preferable that the resin region containing [C] and the resin region containing [D] are adjacent to each other in a layered state to form the boundary surface. The adjacent layered state refers to a state in which both continuous resin regions are adjacent to each other, as shown in Fig. 2, for example, and can be confirmed by observing a cross section obtained by cutting the laminate perpendicular to the planar direction.

[0052] The component [D] of the present invention is a cured product of epoxy resins containing 20 to 50 parts by mass of bisphenol-type epoxy resins having an epoxy equivalent of 400 to 3000 relative to 100 parts by mass of all epoxy resins contained, which is a preferred embodiment since it provides a laminate and molded product with excellent impact bonding strength. A more preferred embodiment is a cured product of epoxy resins containing 20 to 50 parts by mass of bisphenol-type epoxy resins having an epoxy equivalent of 1000 to 3000 relative to 100 parts by mass of all epoxy resins contained.

[0053] The laminate of the present invention can be produced by a molding method such as press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, hand lay-up method, filament winding method, pultrusion method, resin injection molding method, and resin transfer molding method.

[0054] The laminate of the present invention can be produced by laminating the above-mentioned prepreg of the present invention alone or with other prepregs to form at least a part of a layer, and curing the laminate by applying pressure and heat. The method for applying heat and pressure includes, for example, press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc.

[0055] In the laminate of the present invention, the thermoplastic resin of the component [C] is present on the surface or between the layers. It is preferable that the component [C] is present both on the surface and between the layers. The presence of the thermoplastic resin of the component [C] on the surface of the laminate allows the laminate of the present invention to be joined to the same or different members by welding through the component [C], while the presence of the thermoplastic resin of the component [C] between the layers of the laminate provides excellent interlaminar fracture toughness (G IC and G IIC ) is obtained.

[0056] The laminate of the present invention can be integrated (welded) with the laminate through the component [C] by bonding another member, i.e., a member (adherend) of the same type and / or different type as the member constituting the laminate, to the component [C] present on the surface of the laminate by some heating means. Examples of different members (adherends) include members made of thermoplastic resins and members made of metal materials. The member made of thermoplastic resin may contain reinforcing fibers, fillers, etc. The integration method is not particularly limited, and examples thereof include heat welding, vibration welding, ultrasonic welding, laser welding, resistance welding, induction welding, insert injection molding, and outsert injection molding.

[0057] The strength of the joint of the integrated members is preferably 25 MPa or more, more preferably 28 MPa or more, in terms of tensile shear joint strength measured based on ISO4587:1995 (JIS K6850 (1994)). Also, it is preferably 35 MPa or more, more preferably 40 MPa or more, in terms of out-of-plane tensile joint strength measured based on ASTM D7291-07. Furthermore, it is preferably 6 kJ / m 2 It is preferable that the concentration is equal to or higher than 9 kJ / m 2 The higher the bonding strength, the better, and there is no particular upper limit, but in a typical integrated laminate product, the tensile shear bonding strength is 200 MPa, the out-of-plane tensile bonding strength is 300 MPa, and the impact bonding strength is 50 kJ / m 2 is the upper limit. EXAMPLES

[0058] The present invention will be described in detail below with reference to examples. However, the scope of the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various properties were performed under an environment of a temperature of 23°C and a relative humidity of 50% unless otherwise noted.

[0059] <Materials used in the Examples and Comparative Examples> The following components [A], [B], [C], and [D] were used. The components used in each of the examples and comparative examples are as shown in Tables 1 to 3.

[0060] Component [A]: Reinforced fiber T800: Carbon fiber ("TORAYCA (registered trademark)" T800S-24K, manufactured by Toray Industries, Inc., strand tensile strength: 5.9 GPa) T1100: Carbon fiber ("TORAYCA (registered trademark)" T1100G-24K, manufactured by Toray Industries, Inc., strand tensile strength: 7.0 GPa) · T700: Carbon fiber ("TORAYCA (registered trademark)" T700S-24K, manufactured by Toray Industries, Inc., strand tensile strength: 4.9 GPa).

[0061] Component [C]: Thermoplastic resin PA6: Polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc., melting point 225°C)) with a basis weight of 120 g / m 2 Film PP: Polypropylene ("UMEX" (registered trademark) 1010 (manufactured by Sanyo Chemical Industries, Ltd., melting point 142°C)) with a basis weight of 120 g / m 2 film). PEs: Polyester ("Hytrel" (registered trademark) 2551 (manufactured by Toray DuPont Co., Ltd., melting point 164°C)) with a basis weight of 120 g / m 2 film). PPS: Polyphenylene sulfide ("TORELINA" (registered trademark) A670T05 (manufactured by Toray Industries, Inc., melting point 278°C) with a basis weight of 120 g / m 2 Film PEEK: Polyetheretherketone (PEEK 450G (Victrex, melting point 343°C) with a basis weight of 120 g / m 2 of film.

[0062] <Method of producing and evaluating epoxy resin composition> The epoxy resin compositions of the specific examples shown in Table 1 were prepared using the following compounds. (1) Epoxy resin Bisphenol A epoxy resin ("jER" (registered trademark) 825, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 175 (g / eq.)) Phenol novolac epoxy resin ("jER" (registered trademark) 154, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 178 (g / eq.)) Bisphenol A epoxy resin ("jER" (registered trademark) 1001, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 475 (g / eq.)) Bisphenol A epoxy resin ("jER" (registered trademark) 1004, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 925 (g / eq.)) Bisphenol A type epoxy resin ("jER" (registered trademark) 1007, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 1975 (g / eq.). (2) Hardener 4,4'-Diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Kogyo Co., Ltd.) Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation). (3) Curing catalyst 3-(3,4-Dichlorophenyl)1,1-dimethylurea (DCMU99, manufactured by Hodogaya Chemical Industry Co., Ltd.). (4) Viscosity modifier Polyvinyl formal ("Vinylec" (registered trademark) K, manufactured by JNC Corporation). (5) Method for preparing epoxy resin composition The epoxy resin and viscosity modifier shown in Table 1 were put into a kneading device, and heated and kneaded to dissolve the viscosity modifier (however, there are cases where the viscosity modifier is not added). Next, while continuing kneading, the temperature was lowered to 100°C or lower, and an appropriate one selected from the curing agent and curing catalyst shown in Table 1 was added and stirred to obtain epoxy resin compositions B-1 to B-10.

[0063] <Method of producing and evaluating cured epoxy resin> The epoxy resin composition prepared by the above method was poured into a mold, heated in a hot air dryer from 30°C at a rate of 1.5°C / min to the curing temperature listed in Table 1, and then heated and cured for the curing time listed in Table 1, and then cooled to 30°C at a rate of 2.5°C / min to prepare a plate-shaped epoxy resin cured product having a thickness of 2 mm. Component [B] is a cured product of an epoxy resin, and component [D] is a cured product of an epoxy resin. The obtained epoxy resin cured product was evaluated for each of the specific examples listed in Table 1 by the following method.

[0064] <Method of measuring bending strain at break and bending strength of cured epoxy resin> From the plate-shaped resin cured product prepared by the above method, rectangular test pieces 60 mm in length and 10 mm in width were cut out and dried in a vacuum oven at 60°C for 24 hours. A three-point bending test was then carried out using a universal testing machine (Instron Japan Co., Ltd., "Instron" (registered trademark) 5565 model P8564) at a test speed of 2.5 mm / min and a support distance of 32 mm to determine the bending fracture strain and bending strength in accordance with JIS K7171 (1994).

[0065] <Measuring method for melting point of thermoplastic resin> The melting points of thermoplastic resins were measured using a differential scanning calorimeter (DSC) based on JIS K7121 (2012). When multiple melting points were observed for a mixture, the highest melting point was used as the melting point of the thermoplastic resin.

[0066] <How to make prepreg> The prepregs were produced by the following two methods. The components used in each example are shown in Tables 2 and 3.

[0067] Prepreg [I] Reinforced fiber of component [A] (weight 193 g / m 2 ) is pulled out from the continuous reinforcing fiber sheet aligned in one direction, and while running in one direction, a reinforcing fiber sheet having a basis weight of 120 g / m2 composed of the component [C] is 2 The resin sheet was placed on the continuous reinforcing fiber sheet, heated with an IR heater to melt the component [C], and adhered to the entire surface of one side of the continuous reinforcing fiber sheet. Pressurized with a nip roll whose surface temperature was kept below the melting point of the component [C], the impregnated reinforcing fiber sheet was cooled to obtain a fiber-reinforced resin intermediate. The epoxy resin composition related to the component [B] selected as shown in Tables 2 and 3 was applied to a sheet having a resin basis weight of 100 g / m using a knife coater. 2 The epoxy resin composition was applied to a release paper to prepare an epoxy resin film, and the epoxy resin film was then placed on the surface of the intermediate opposite to the surface impregnated with the component [C]. The intermediate was impregnated with the epoxy resin composition while being heated and pressurized with a heat roll, thereby obtaining a prepreg [I].

[0068] Prepreg [II] The epoxy resin composition related to the component [B] selected as shown in Tables 2 and 3 was applied to a coating machine with a resin weight of 50 g / m 2 The resin film was coated on a release paper with the reinforcing fiber of the component [A] aligned in one direction (weight per unit area: 193 g / m 2 The carbon fibers were impregnated with the epoxy resin composition while being heated and pressurized using heat rolls, to obtain prepreg [II].

[0069] <Laminate manufacturing method and mechanical property evaluation> (1) Measurement method for tensile shear bond strength The prepregs [I] and [II] prepared above were cut to a predetermined size to obtain two prepregs [I] and six prepregs [II]. The axial direction of the reinforcing fibers was defined as 0°, and the direction perpendicular to the axis was defined as 90°, so [0° / 90°] 2s (The symbol s indicates mirror symmetry) was laminated to prepare a preform. At this time, the two outermost layers on each side of the preform were laminated to be prepregs [I]. That is, the two prepregs [I] were laminated to sandwich six prepregs [II]. The preform was arranged so that both surface layers were thermoplastic resin layers containing the component [C]. That is, the surface of the prepreg [I] impregnated with the component [C] was arranged to be on the outside. This preform was set in a press molding die, and a pressure of 0.6 MPa was applied with a press machine while maintaining this shape using a jig or spacer as necessary, and a laminate was obtained by heating under the conditions described in Tables 2 and 3. The component [C] was present on the surface of the laminate.

[0070] The obtained laminate was cut into two pieces with a width of 250 mm and a length of 92.5 mm, with the 0° direction as the length direction of the test piece, and dried in a vacuum oven for 24 hours. The two panels cut into a width of 250 mm and a length of 92.5 mm were then stacked together with a width of 25 mm and a length of 12.5 mm, with the 0° direction as the length direction, and a pressure of 3 MPa was applied at a temperature 20° C. higher than the melting point of the thermoplastic resin of the component [C] used, and held for 1 minute to weld the stacked surfaces together to obtain an integrated molded product. A tab was attached to the obtained integrated molded product in accordance with ISO4587:1995 (JIS K6850 (1994)), and the product was cut to a width of 25 mm to obtain the desired test piece.

[0071] The obtained test pieces were dried in a vacuum oven for 24 hours, and the tensile shear bond strength was measured at an environmental temperature of 23°C based on ISO4587:1995 (JIS K6850 (1994)). The results were evaluated as follows. The results are shown in the table. 28MPa or more:A 25MPa or more and less than 28MPa: B 20MPa or more but less than 25MPa: C Less than 20MPa: D (fail).

[0072] (2) Measurement method for impact joint strength The prepregs [I] and [II] prepared above were cut to a predetermined size, and the two outermost layers on each side of the preform were prepregs [I], with 50 prepregs [II] sandwiched between them, and a total of 52 sheets were laminated so that all had the same reinforcing fiber direction to produce a preform. At this time, both surface layers of the preform were arranged to be thermoplastic resin layers containing the component [C]. In other words, the surface of the prepreg [I] impregnated with the component [C] was arranged to be on the outside. Similarly, the two outermost layers on each side of the preform were prepregs [I], with 103 prepregs [II] sandwiched between them, and a total of 105 sheets were laminated so that all had the same reinforcing fiber direction to produce a preform. In other words, the surface of the prepreg [I] impregnated with the component [C] was arranged to be on the outside. These two types of preforms were set in press molding dies, and while maintaining this shape using jigs and spacers as necessary, a pressure of 0.6 MPa was applied with a press machine, and two types of laminates with thicknesses of approximately 10 mm and approximately 20 mm were obtained by heating under the molding conditions shown in Tables 2 and 3. The component [C] was located on the surface of the laminate.

[0073] The obtained laminate with a thickness of about 10 mm was cut into a rectangular shape with a width of 250 mm and a length of 25 mm, with the axial direction of the reinforcing fibers as the length direction of the test piece. Furthermore, the obtained laminate with a thickness of about 20 mm was cut into a rectangular shape with a width of 250 mm and a length of 45 mm, with the axial direction of the reinforcing fibers as the length direction of the test piece, and the obtained two panels were dried in a vacuum oven for 24 hours. Thereafter, the two panels were overlapped with the same reinforcing fiber axial direction, and the joining surfaces were welded by applying a pressure of 3 MPa at a temperature 20 ° C higher than the melting point of the thermoplastic resin of the component [C] used and holding it for 1 minute, thereby obtaining an integrated molded product. The obtained integrated molded product was cut to a width of 25 mm to obtain the target test piece.

[0074] The obtained test pieces were dried in a vacuum oven for 24 hours, and the impact bonding strength was measured based on JIS K6855 (1994) with the surface perpendicular to the reinforcing fiber axis direction being the surface receiving the impact, and the test results were evaluated as follows. The results are shown in the table. 9kJ / m 2 Above: A 6kJ / m 2 More than 9kJ / m 2 Less than: B 3kJ / m 2 More than 6kJ / m 2 Less than: C 3kJ / m 2 Less than: D (Fail).

[0075] (3) Method for measuring out-of-plane tensile bond strength The prepregs [I] and [II] prepared above were cut to a predetermined size, and the two outermost layers on each side of the preform were prepregs [I], with 73 prepregs [II] sandwiched between them, and a total of 75 sheets were laminated so that all had the same reinforcing fiber direction to prepare a preform. At this time, the two outermost layers on each side were laminated so that they were prepregs [I], and both surface layers of the preform were arranged so that they were thermoplastic resin layers containing the component [C]. This preform was set in a press molding die, and if necessary, a jig or spacer was used to maintain this shape, and a pressure of 0.6 MPa was applied with a press machine, and the laminate was obtained by heating under the molding conditions described in Table 2 or 3. The location of the component [C] was the surface of the laminate.

[0076] The obtained fiber-reinforced composite plate was cut into two rectangular pieces, 250 mm wide and 125 mm long, with the reinforcing fiber axis as the length direction of the test piece, and dried in a vacuum oven for 24 hours. The two panels were then stacked with the same reinforcing fiber axis direction, and the joint surfaces were welded by applying a pressure of 3 MPa at a temperature 20°C higher than the melting point of the thermoplastic resin of the component [C] used and holding it for 1 minute, thereby obtaining an integrated molded product. The obtained integrated molded product was ground into a spool shape with an outer diameter of 25 mm, an inner diameter of 19 mm, and a gauge length of 6.4 mm, to obtain the desired test piece.

[0077] The obtained test pieces were dried in a vacuum oven for 24 hours, and the out-of-plane tensile bond strength was measured according to ASTM D7291-07. The results were evaluated as follows. The results are shown in the table. 40MPa or more: A 35MPa or more and less than 40MPa: B 30MPa or more and less than 35MPa: C Less than 30MPa: D (fail).

[0078] (4) Interlaminar fracture toughness (G IC and G IIC ) Measurement method The prepreg [I] prepared above was cut to a predetermined size, and all prepregs were laminated with the surface with the component [C] facing upward so that the reinforcing fiber direction was the same, and a total of 20 sheets were laminated. At this time, a release film for preliminary crack introduction was sandwiched between the 10th and 11th sheets in the center to prepare a preform. This preform was set in a press molding die, and a pressure of 0.6 MPa was applied with a press machine while maintaining this shape using a jig or spacer as necessary, to obtain a laminate under the molding conditions described in Table 2 or 3. The component [C] was present between the layers of the laminate and on one surface.

[0079] From the obtained laminate, rectangular test pieces of 150 mm in length and 20 mm in width were cut out with the reinforcing fiber axis in the longitudinal direction of the test pieces, and were dried in a vacuum oven at 60°C for 24 hours. The obtained test pieces were subjected to the interlaminar fracture toughness (G IC and G IIC ) was evaluated.

[0080] <Measurement of the mean roughness length RSm and mean roughness height Rc of prepreg or laminate> The prepreg [I] or laminate prepared above is used. As shown in FIG. 1, in the case of the prepreg, an image of 1000 times magnification was taken using an optical microscope at an observation cross section 5 cut perpendicular to the prepreg plane direction at an angle of 45 degrees at the starting point perpendicular to the prepreg plane direction in a plan view of the prepreg with respect to the fiber direction 4 of any [A] contained in both resin regions. In an arbitrary observation range of 500 μm square in the obtained image, the roughness average length RSm and roughness average height Rc of the cross-sectional curve element obtained by the cross-sectional curve element measurement method 1, as defined in JIS B0601 (2001), were measured. The same applies to the laminate.

[0081] <Examples 1 to 14> In Examples 1 to 14, laminates were produced by the method described in (1) Measuring method for tensile shear bond strength, (2) Measuring method for impact bond strength, and (3) Measuring method for out-of-plane tensile bond strength.

[0082] <Example 1 and Comparative Examples 1 and 2> In Example 1, as shown in Table 2, by using an epoxy resin having an average epoxy value of 3.9 meq. / g as component [B], the impact bond strength and out-of-plane tensile bond strength of the integrally molded product were superior to those of Comparative Example 1 and Comparative Example 2 shown in Table 3.

[0083] <Examples 1 to 6> As shown in Table 1, epoxy resins with different average epoxy values ​​were used in Examples 1 to 6. As shown in Table 2, as the average epoxy value increased, the impact bonding strength tended to decrease slightly, and as the average epoxy value decreased, the out-of-plane tensile bonding strength tended to decrease slightly. However, within the average epoxy value ranges in Examples 1 to 6, all of the resins showed excellent various bonding strengths.

[0084] <Examples 1 and 7> As shown in Table 1, a curing agent different from that used in Example 1 was used in Example 7. However, as shown in Table 2, similar to Example 1, various excellent bonding strengths were exhibited.

[0085] <Example 1 and Example 8> As shown in Table 1, Example 8 was produced in the same manner as Example 1, except that no viscosity modifier was used. As shown in Table 2, Example 8 showed various excellent bonding strengths similar to Example 1.

[0086] <Example 1, Example 9, and Example 10> As shown in Table 2, in Examples 9 and 10, reinforcing fibers with different strand tensile strengths were used. Compared to Example 1, the higher the strand tensile strength, the more improved the tensile shear bond strength and out-of-plane tensile bond strength, demonstrating favorable characteristics.

[0087] <Example 1 and Examples 11 to 14> As shown in Table 2, in Examples 11 to 14, a different component [C] from that in Example 1 was used, but similar to Example 1, various excellent bonding strengths were exhibited.

[0088] <Example 1 and Comparative Example 3> In Comparative Example 3, a film with a basis weight of 50 g / m was applied to both sides of a reinforcing fiber sheet arranged in a unidirectional plane. 2 A film of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc.)) was attached to the sheet, and the sheet was heated and pressed at 250°C to give a reinforced carbon fiber basis weight of 193 g / m. 2 The prepreg obtained was cut to a predetermined size and split into [0° / 90°] pieces for evaluating the tensile shear bond strength. 2sThe laminated sheets were laminated in the above configuration. For the impact bonding strength evaluation, two types of prepregs were used: a total of 52 prepregs laminated in the same reinforcing fiber direction, and a total of 105 prepregs laminated in the same reinforcing fiber direction. For the out-of-plane tensile bonding strength evaluation, 75 prepregs were laminated in the same reinforcing fiber direction. Each prepreg obtained after lamination was subjected to a pressure of 3 MPa with a press machine and heated at 250 ° C for 10 minutes to obtain each laminate plate. The tensile shear bonding strength, impact bonding strength, and out-of-plane tensile bonding strength were measured from the obtained laminate by the method described in the Examples. As shown in Table 3, the laminate plate of Comparative Example 3 did not contain epoxy resin, so that the out-of-plane tensile strength was lower than that of Example 1, and did not show sufficient properties as a structural material.

[0089] <Example 15 and Comparative Examples 4 and 5> In Example 15, (4) Interlaminar fracture toughness value (G IC and G IIC ) to prepare a laminate. The prepreg [I] was cut to a predetermined size, and 20 sheets of all prepregs were laminated with the surface with the component [C] facing upward so that the reinforcing fiber direction was the same, and a release film for preliminary crack introduction was sandwiched between the 10th and 11th sheets in the center to prepare a preform. In Comparative Example 4, prepreg [II] (not containing component [C]) was cut to a predetermined size, laminated in the same manner as in Example 15, and a release film was sandwiched to obtain a preform. In Comparative Example 5, polyamide particles (SP-500, manufactured by Toray Industries, Inc.) were applied to one surface of prepreg [II] (not containing component [C]) cut to a predetermined size, and the amount of particles per unit area of ​​the prepreg was 7 g / m. 2 After uniformly dispersing the mixture, the mixture was laminated in the same manner as in Example 15, and a release film was sandwiched between the layers to obtain a preform. In both Example 15 and Comparative Examples 4 and 5, the obtained preform was subjected to a pressure of 0.6 MPa in a press and heated at 135°C for 120 minutes to obtain a laminate, and the interlaminar fracture toughness (G IC and G IIC) was evaluated. As shown in Tables 2 and 3, Example 15, which contains the component [C] between the layers of the laminate, exhibited a superior interlaminar fracture toughness value compared to Comparative Example 4, which does not contain the component [C], and Comparative Example 5, which contains a thermoplastic resin in a different form.

[0090] [Table 1]

[0091] [Table 2-1]

[0092] [Table 2-2]

[0093] [Table 3] [Explanation of symbols]

[0094] 1: A layer constituting a prepreg or laminate 2: Component [A] 3: Component [C] and Component [B] or Component [C] and Component [D] 4: Axial direction of any fiber bundle 5: Observation cross section 6: Component [A] 7: Resin region containing component [C] 8: Resin region containing component [B] or resin region containing component [D] 9: Observation image 10: Boundary 11: Reference line 12: Orthobase line 13: Cross section curve

Claims

1. A prepreg comprising the following components [A], [B] and [C]: The average epoxy value of all the epoxy resins contained in [B] is 2.0 meq. / g or more and 5.0 meq. / g or less, [C] is present on the surface of the prepreg, A prepreg in which the reinforcing fibers [A] contained in both resin regions are present across the boundary between a resin region containing [B] and a resin region containing [C], and the boundary is formed by the resin region containing [B] and the resin region containing [C] being adjacent to each other in layers. [A] Reinforced fiber [B] Epoxy resin [C] Thermoplastic resin

2. 2. The prepreg according to claim 1, wherein, in a plan view of the prepreg, when a cross section perpendicular to a prepreg plane including the [A] is obtained from a direction at an angle of 45 degrees different from the fiber direction of any [A] contained in both resin regions, the cross section formed by the boundary surface where the two resin regions are in close contact has a roughness average length RSm defined in JIS B0601 (2001) of 100 μm or less and a roughness average height Rc of 3.5 μm or more.

3. 3. The prepreg according to claim 1 or 2, wherein the average epoxy value of all epoxy resins contained in the component [B] is 2.5 meq. / g or more and 4.0 meq. / g or less.

4. 4. The prepreg according to any one of claims 1 to 3, wherein component [B] contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 400 or more and 3,000 or less, relative to 100 parts by mass of all epoxy resins contained therein.

5. 5. The prepreg according to claim 4, wherein the component [B] contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol type epoxy resin having an epoxy equivalent of 1,000 or more and 3,000 or less relative to 100 parts by mass of all epoxy resins contained.

6. 6. The prepreg according to claim 1, wherein the component [B] has a bending fracture strain of 8% or more when the degree of cure is 90% or more.

7. 7. The prepreg according to claim 1, wherein the component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.

8. The prepreg according to any one of claims 1 to 7, wherein the roughness average height Rc is 10 µm or more.

9. A laminate including layers containing the following components [A], [C] and [D]: [D] is a cured product of an epoxy resin in which the average epoxy value of all the epoxy resins is 2.0 meq. / g or more and 5.0 meq. / g or less, A laminate in which the reinforcing fibers [A] contained in both resin regions are present across the boundary between a resin region containing [C] and a resin region containing [D], and the boundary is formed by the resin region containing [C] and the resin region containing [D] being adjacent to each other in layers. [A] Reinforced fiber [C] Thermoplastic resin [D] Epoxy resin cured product

10. 10. The laminate according to claim 9, wherein, in a plan view of the laminate, when a cross section perpendicular to the plane of the laminate including the [A] is obtained from a direction at an angle of 45 degrees different from the fiber direction of any [A] contained in both resin regions, the cross section formed by the boundary surface where the two resin regions are in close contact has a roughness average length RSm defined in JIS B0601 (2001) of 100 μm or less and a roughness average height Rc of 3.5 μm or more.

11. The laminate according to claim 9 or 10, wherein the component [C] is present on the surface.

12. The laminate according to any one of claims 9 to 11, wherein a component [C] is present between the layers.

13. 13. The laminate according to any one of claims 9 to 12, wherein the component [D] is a cured product of an epoxy resin containing 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 1,000 or more and 3,000 or less, relative to 100 parts by mass of the total epoxy resins contained.

14. The laminate according to claim 9 , wherein the roughness average height Rc is 10 μm or more.

15. 15. The laminate according to any one of claims 9 to 14, wherein component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.

16. The laminate according to claim 11 or 12, which is a laminate in which a cured product of the prepreg according to any one of claims 1 to 8 constitutes at least a part of a layer.

17. A molded article, wherein another member is integrated with the laminate according to any one of claims 11 to 16 by being bonded to a surface of the component [C].

Citation Information

Patent Citations

  • Composite material

    JP1989104625A

  • Prepreg and fiber-reinforced composite material

    JP1996259713A

  • Epoxy resin composition, prepreg and fiber-reinforced composite material

    JP1996337707A

  • Carbon fiber reinforced resin molded product and its manufacture

    JP1998138354A

  • Epoxy resin composition, resin cured product, prepreg and fiber reinforced composite

    JP2003201388A